Project-Based Learning on Science Process Skills and Learning Outcomes in High School Physics: A Quasi-Experimental Study on the Topic of Fluids - Luh Gede Sutaryani; Ni Made Pujani; I Nyoman Tika (LPPM Undiksha, 2024)
This research was motivated by the low science process skills (KPS) and student learning outcomes on the topic of fluids at the high school level. The main purpose of this study is to examine the impact of the implementation of the Project-Based Learning (PjBL) model on improving PPP and student learning outcomes. The type of research used is quasi-experiment, involving two groups, namely an experimental class that applies PjBL and a control class that uses direct learning methods. The study population was high school students with a randomly selected sample. Data were collected through objective tests and essays to measure KPS and student learning outcomes, then analyzed using descriptive statistical analysis and Multivariate Analysis of Covariance (MANCOVA). The results show that the implementation of PjBL has a significant positive impact on improving PPP and student learning outcomes compared to direct learning methods. The conclusion of this study is that the PjBL model is an effective pedagogical approach in improving students' science process skills and learning outcomes on fluid topics. The implications of this study show that PjBL can be a recommended learning strategy to improve the quality of science education in high school.